2021
DOI: 10.1108/jfra-01-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing corporate sustainability disclosure practices: empirical evidence from Indian National Stock Exchange

Abstract: Purpose This study aims to evaluate the nature and extent of sustainability disclosure practices of publicly listed companies in India. Further, it investigates the impact of potential determinants on the sustainability disclosure of companies. Design/methodology/approach The study analyzes data of 75 top listed nonbanking companies operating in India included in NIFTY100 Index for the years 2014-2015 to 2018-2019. In the present study, environment, social and governance disclosure dimensions were considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 80 publications
3
39
0
2
Order By: Relevance
“…, 2019). Sustainability reporting domain is still in the formative stage in developing country like India (Kumar et al. , 2021), and only few studies have examined the sustainability reporting practices of companies operating in India (Kumar and Prakash, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2019). Sustainability reporting domain is still in the formative stage in developing country like India (Kumar et al. , 2021), and only few studies have examined the sustainability reporting practices of companies operating in India (Kumar and Prakash, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The review of extant literature suggests that, although prior studies have empirically examined the link between corporate governance and sustainability reporting in the context of developed countries (Jizi et al, 2014;Figueira et al, 2018;Garcia et al, 2019), the studies exploring the same based on developing countries are limited (Mahmood and Orazalin, 2017;Alshbili et al, 2019). Sustainability reporting domain is still in the formative stage in developing country like India (Kumar et al, 2021), and only few studies have examined the sustainability reporting practices of companies operating in India (Kumar and Prakash, 2020). Moreover, a study providing empirical evidence about the impact of governance attributes on sustainability reporting of companies operating in India is nonexistent, to the best of authors' knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Injeni et al, 2021;Tilt et al, 2021;Jain et al, 2021), while others use other measures of SPD such as disclosure indices obtained from other studies and reporting frameworks (e.g. Khan et al, 2021;Cicchiello et al, 2021;Kumar et al, 2021). We also note that majority of the studies use content analysis methodologies (e.g.…”
Section: Literature Review and Hypotheses Development 21 Literature R...mentioning
confidence: 97%
“…As per legitimacy theory older firms are likely to disclose much more information on CSR/ sustainability in their reports to legitimise their existence in the society [34][35][36] . Most of the researchers found a positive relationship between firm age and the level of CSR and sustainability reporting [18][19][20][21]35 . Very few studies have found insignificant or negative association between age and level of corporate disclosure 10,12,16 .…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%